Human Capital in Relation to Industry 4.0 - Jaroslav VRCHOTA; Petr ŘEHOŘ; Ladislav ROLÍNEK; Jiří BEDNÁŘ; Radek TOUŠEK (Communications of International Proceedings, 2021)
The fourth industrial revolution has an impact on the labor market, namely on existing professions and also gives rise to new ones. New principles of work organization will be promoted and the whole structure of the labor market will change. The threat of the disappearance of a high percentage of jobs is one of the greatest risks of the Industry 4.0. Human resource management must address the impact of Industry 4.0 on human resources, and it must look for ways and help companies eliminate these negatives. Czech literature, as well as foreign literature, still lacks research into the impacts of Industry 4.0 on human resource management. The aim of the paper is to assess the companies' approach to human capital in relation to Industry 4.0. Where 115 manufacturing companies were interviewed. The results showed that the main reason for the implementation of Industry 4.0 is the lack of employees, which is subsequently related to the lack of skilled workers..
Keywords: Industry 4.0; human resources; skilled workers; strategy